Various Book Reviews - Editor, The (Himalayan Journal of Sociology and Anthropology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> Biswo Kallyan Parajuli(ed). Sociology and Anthropology in Nepal, Department of Sociology & Anthropology, Prithwi Naryan Campus,2008, 169pp, Rs 250(pb) Rafael J. Engel and Russell K. Schutt : The Practice of Research in Social Work Sage Publication, Thousand Oaks, California USA (2005) Price NRs 3508 (Soft Cover) PP 554, XXI Hemant R. Ojha, Netra P. Timsina, Ram B. Chhetri, Krishna P. Paudel (ed.). Knowledge System and Natural Resources, Management, Policy and Institutions in Nepal, Cambridge University Press India Pvt. Ltd.,2008, p.p. 173, ISBN: 978-81-7596-563-8, Price not quoted. Kailash Nath Pyakuryal, PhD, Bishnu Raj Upreti, PhD Sager Nath Sharma, PhD. (ed). Nepal: Transition to Transformation, Published by NCCR North South, June 2008. Page 234, ISBN: 978-9937-2-0602-0, Price not quoted. Prof. Chaitanya Mishra, The Essays on the Sociology of Nepal Published by FinePrint Inc., Anamnagar, Kathmandu Nepal, 2007. Page 363, ISBN: 99946-2-321-4, Price Rs. 450. DOI: http://dx.doi.org/10.3126/hjsa.v3i0.1502 Himalayan Journal of Sociology and Anthropology Vol.III, Sept. 2008 p.148-165